Trends in the abundance of diving ducks and seaducks wintering in Japan - Shimada, Tetsuo; Mori, Akira; Higuchi, Hiroyoshi (Wildfowl, 2016)
Japan is an important wintering area for many Asian diving duck and seaduck populations, although their status and trends in abundance are poorly known and previously undescribed. Trends in annual abundance therefore were analysed for nine common diving and seaduck species wintering in the country, using data from the national waterbird surveys undertaken annually by volunteers and coordinated by the Ministry of the Environment and local prefectures over the past 46 years. Annual indices and short-term (16 years: 2000â€“2015), medium-term (26 years: 1990â€“2015) and long-term (36 years and 46 years to 2015) trends in numbers were calculated for each species using TRIM software. The indices recorded for Long-tailed Duck Clangula hyemalis, Harlequin Duck Histrionicus histrionicus, Black Scoter Melanitta americana and Red-breasted Merganser Mergus serrator all exhibited significant long-term declines; Common Goldeneye Bucephala clangula and Common Pochard Aythya ferina showed moderate declines over the 26-year period; and Greater Scaup A. marila declined during 2000â€“2015. Numbers of Tufted Duck A. fuligula increased significantly over 36- and 26-year time-scales, but it was found to be â€œstableâ€ over the most recent 16 years. Velvet Scoters Melanitta fusca have tended to decrease since their peak abundance in 1977, although TRIMâ€™s criteria indicated that the trend was â€œuncertainâ€.